(untitled) (REMUNOM, 2025)
Visual impairment corresponds to a partial or total loss of an individual’s visual capacity. The challenges faced range from physical and social barriers and limitations in the practice of routine activities such as maintaining adequate oral hygiene and frequent visits to the dental office. Due to the lack of information and inclusive social programs, they become targets of oral pathologies. This study aimed to carry out a bibliographical review of the main oral health conditions found in patients with visual impairment and the difficulties faced during dental care. An integrative literature review was carried out based on studies published and indexed in the electronic databases PubMed/Medline (National Library of Medicine), SciELO (Scientific Electronic Library Online), Lilacs (Latin American and Caribbean Literature in Health Sciences ), Science Direct (Elsevier), Scopus (SciVerse Scopus), Embase (Elsevier) and Periódicos Capes, using the keywords: “People with visual impairment”/ “Visually Impaired Persons”, “Oral health”/“Oral health” and “Dentistry”/“Dentistry”, through the advanced search feature, between 2019 and 2023. 24,343 studies were identified, but after applying the eligibility criteria, 10 studies remained to compose the present review. After analyzing the publications, it was found that the lack of accessibility and mobility to perform dental care influence the maintenance of adequate oral health and the lack of encouragement and guidance on hygiene techniques adapted to their ocular limitations. Therefore, it is necessary to implement health education methods such as Braille and playful materials.